Elaboración de un cuadro de mando integral para la estación se servicio toacazo año 2015 - Herrera Chacha, Myrian Fabiola (2015)
The thesis is presented for our degree proposes the design (Balanced Scorecard) to the Service Station Toacazo, which is a control tool used to achieve continuous improvement in each of the areas of the organization and reform institutional management, integrating monitoring measures across four basic perspectives such as: financial, customer, internal processes, learning and growth. This methodology translates strategy into a coherent set of indicators to achieve institutional vision. The first chapter contains the theoretical basis related to each of the main categories starting with the company, administrative management, strategic planning, value chain and elements containing the Balanced Scorecard. In chapter two a diagnosis of the current situation of the station is done through direct observation, interviews and analysis of the respective organizational environments: Macro environment and microenvironment, and the internal environment of the company in this SWOT